The efficacy of psychodynamic psychotherapy for young adults: a systematic review and meta-analysis - Trotta, Antonella; Gerber, Andrew J.; Rost, Felicitas; Robertson, Sarah; Shmueli, Avi; Perelberg, Rosine J. (Frontiers in Psychology, 2024)
Objective: One in six young adults presents with at least one mental health problem. However, so far, little attention has been directed to the mental health needs and the efficacy of therapeutic interventions for young adults. We conducted a systematic review and meta-analysis of the type, quality and efficacy of psychoanalytic psychotherapy for young people. Method: We searched ​the ​PsycInfo, PubMed, Embase, and Cochrane databases to identify all ​the ​published randomized controlled trials (RCT), ​and ​naturalistic and observational studies of psychodynamic or psychoanalytic psychotherapies. We calculated the standardised mean difference in scores of psychodynamic interventions versus control conditions, adopting a random effects model (Hedges’ g). Results: We identified 22 eligible studies, including 14 RCTs, and 8 naturalistic studies. Statistical analyses showed no significant difference between psychodynamic psychotherapy and other comparison treatments (psychotherapy or pharmacological interventions) for young adults (Hedges’g -0.34 [95% CI: -0.991;-0.309], p=0.304). Nevertheless, there was a significant effect of psychodynamic psychotherapy when compared with control conditions (waiting list or treatment as usual) for target symptoms (Hedges’g -1.24 [95% CI: -1.97;-0.51], p<0.001). Conclusions: Our systematic review highlights important clinical implications in identifying the efficacy of psych​o​analytic interventions for specific at-risk groups and ​suggests​​ ​develop​ing​ prevention strategies for mental health problems in young adulthood across cultures and context.